UJI KARAKTERISTIK PEMBAKARAN HASIL DESTILASI KARET BEKAS-MINYAK DIESEL DENGAN MENGGUNAKAN DROPLET - Aji Indra Hartono; Aqli Mursadin (Universitas Lambung Mangkurat, 2019)
This study aims to look at the combustion characteristics of destillates of used rubber and diesel oil using droplet, the characteristics observed were flash point, ignition delay time, burning rate, and visualization (hight) of fire. Variation in mix RCO 10%, 20%, 30%, 40%, 50%. The tool used is a tool designed by researchers. The result of the flash point study found that the highest velue was found in the mixture of RCO 10% which was 105,7oC and the lowest value was found in mixture of 50% which was 56,6oC. then the highest value of the ignition delay time is in the mixture of 10% which is 1,64 seconds and the lowest value in the mixture is 30% which is 0,98 seconds, then are result of the highest burning rate are found in the mixture 0f 40% which is 3,83 seconds and lowest value is mixed with 20% which is 3,1 second. Then the highest level of fire in the mixture of 10% is 82,3 mm and the lowest is in the mixture of 50% which is 73,2 mm. Keywords: Rubber Compound Oil, Droplet, Flash Point, Ignition Delay Time, Burning Rate